The Moderasi beragama sebagai paradigma baru pendidikan Islam: Strategi menangkal polarisasi sosial diera digital dan post-Truth - Nabilla Rizki Syawali; Muti'a Muti'a; Herlini Puspika Sari (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
The digital age and the phenomenon of post-truth have created new challenges for Islamic education, where it is becoming increasingly difficult to control the distortion of religious narratives and social polarization in cyberspace. The crisis of religious authority and the spread of misinformation demand a new paradigm in the educational system. This study aims to analyze the relevance of religious moderation as a new basis for Islamic education in order to combat strategies of social segregation in an era of disruption. The research method used is a qualitative documentary study, with critical analysis of various academic publications, government policies, and contemporary social phenomena. The results indicate that strengthening religious moderation as an educational paradigm requires three main teaching strategies. First, integrating the values ​​of wasatiyah (religious authority) through positive learning methodologies and active dialogue to develop students' critical thinking against extremist narratives. Second, introducing digital literacy based on prophetic values ​​and the ethics of Islamic communication (qalamun ma’rufan) as a filter for information on social networks. Third, to strengthen an inclusive educational ecosystem through collaboration between educational institutions, families, and communities. This study concludes that establishing religious moderation as a new paradigm is not only a preventive measure but also an important pedagogical transformation for creating a tolerant and digitally literate society capable of maintaining national stability amidst the complexities of the post-truth era.